PARAMETER KEBENARAN ILMU PENGETAHUAN (SAINS) DALAM AL-QUR’AN - Endah Tri Wisudaningsih; Musyafi’ (Al-Fikru : Jurnal Pendidikan Dan Sains, 2020)
The truth of a science can truly be known. Truth is the culmination of the study of epistemology which boils down to metaphysics. The essence of a scientific truth is the compatibility of information, or theory with the reality of the object itself. In aspects of the metaphysical world and absolute reality transcendental, the truth parameter is the text of revelation (al-Qur'an and Hadith) whose meaning is known exactly according to the standard of Ijma 'and logic for the degree of "normal". The parameters of the truth of a science can be proven in the Qur'an, which contains various sciences whose absolute truth and authenticity cannot be doubted and have also given a special position to the Qur'an among other holy books. Keywords: Al-Qur'an, Science, Truth, Theory of Religion